Participation rate by gender in Malaysia's workforce / Suhaida Mohd Amin and Mohd Faizal P. Rameli - Mohd Amin, Suhaida; P. Rameli, Mohd Faizal (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Workforce or Labour force is a key component in long term economic growth, almost as important as productivity. A common theory in modem economics claims that besides the economic variable, there as other factor of an institutional, legal or attitudinal nature which can explain the changes in participation rate of labour. In the West during the later half of the 20th century, the labour force participation rate increased significantly, largely due to the increasing number of women entering the workplace. Most studies indicate that male labour force is quite intensive to change in wage rate whereas female labour force is fairly responsive to change in wage rate. However, secular trend shows that while the number of labor force increases due to the increases in population, labour force participation rate for male and female has no significant relationship. This paper will give an input for who/what actually is the labour force and the labour force participation rate, the secular trend of labour force participation rate and factor contributing to the declining or rising for this indicator. Besides, this paper will focus on the labour force participation rate by gender in Malaysia from year 1982 to 2009.